Why simple wins : escape the complexity trap and get to work that matters - Bodell, Lisa (Bibliomotion, 2017)
Using simple stories and techniques, this inspiring book shows that by using simplicity as an operating principle, we can eliminate the busy work that puts a chokehold on us every day, and instead spend time on the work that we value. --